Best Answer

10x + 41y - 142x + 2y

= 10x - 142x + 41y + 2y

= (10 -142)x + (41 + 2)y

= -132x + 43y

Q: Simplify 10x plus 41y-142x plus 2y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

6x-2y

To solve this, you would normally set up a systems of equations 10x + 2y = 10 10x + 2y = 11 However, it clearly makes no sense and has no answer. To prove this mathematically, subtact the two equations. 10x - 10x = 0 2y - 2y = 0 10-11 = -1 Therefore, it is basically saying that 0 + 0 = -1 Obviously, that is incorrect, so this question has no solutions.

2y

the answer to this problem is -2x^2y^2

Related questions

10x + 41y142x + 2y

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

6x-2y

To solve this, you would normally set up a systems of equations 10x + 2y = 10 10x + 2y = 11 However, it clearly makes no sense and has no answer. To prove this mathematically, subtact the two equations. 10x - 10x = 0 2y - 2y = 0 10-11 = -1 Therefore, it is basically saying that 0 + 0 = -1 Obviously, that is incorrect, so this question has no solutions.

2y

10x - 5y + 2x - 3y = 12x - 8y

the answer to this problem is -2x^2y^2

8y-7x

Bbbbf

3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y

Y plus Y = 2Y simplified

3y+2z